2019
DOI: 10.1155/2019/1542797
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Microscopic Stress Mechanism for the Microscopic Pore Deformation during Soil Compression

Abstract: Pore structure is closely related with strength, constitutive relation, consolidation characteristics, and permeability properties of soil. Consequently, improving the understanding of the relationship between microscopic structure and macroscopic physical and mechanical properties has extremely important scientific significance. A large number of studies have shown that pores of soil have fractal features, and hence, the carpet model can be used to approximately simulate the fractal structure of clay. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A large number of studies have shown that geotechnical media represents obvious fractal features [36][37][38][39][40][41][42][43]. e use of the weight distribution of the particle sizes is therefore appropriate.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…A large number of studies have shown that geotechnical media represents obvious fractal features [36][37][38][39][40][41][42][43]. e use of the weight distribution of the particle sizes is therefore appropriate.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…The influence of fine grain content and dry density of two kinds of coarse-grained soil on the shear strength parameters and the variation of shear strength parameters were studied by direct shear test by Li & Xing (2006). Tao, Peng, Xiao, Wu, & Chen (2019) studied the changes of microscopic pore of numerical simulation and that of physical experiment during compression of clay. Ling, Fu, Han, & Wang (2010) studied the effects of particle size distribution and particle breakage on the static and dynamic characteristics of rockfill.…”
Section: Introductionmentioning
confidence: 99%